The relationship between working environment and job satisfaction among public sector employees at Pejabat Kesihatan Bahagian Samarahan, Sarawak / Nur Nadzirah Nordin - Nordin, Nur Nadzirah (2018)
The purpose of this paper is to identify the relationship between working environment and job satisfaction among public sector employees at Pejabat Kesihatan Bahagian Samarahan, Sarawak. It is hypothesized that working environment has a positive influence on job satisfaction. Results were analyzed with normality test, reliability analysis and correlation. This study has been focused on 80 employees in Pejabat Kesihatan Bahagian Samarahan, Sarawak. The results of this study show that working environment possesses significant positive relationships towards employee's job satisfaction at Pejabat Kesihatan Bahagian Samarahan, Sarawak. This paper also presents recommendations and suggestion for further research.